KELUARGA KRISTEN BERBASIS KERAJAAN ALLAH DI JEMAAT GBI ROCK SATELIT KOTA DENPASAR - Roy Pieter (Diegesis : Jurnal Teologi, 2020)
The family is the oldest institution in the world since God created the heavens and the earth. The family is an extension of the kingdom of God. Every family must walk in the divine order. God's order for the family and its description can be found in the book of Ephesians. This study aims to determine the application of the principles of the kingdom of God in families in the congregation GBI ROCK Denpasar City Satellite The research method used in this study is qualitative, the sample data source in this study is family -family who congregates in GBI ROCK satellite Kota of Denpasar. The sample data source in this study was selected purposively and snowball sampling. The data collection techniques used in this study were interviews and observation. Data analysis is performed interactively through a process of data reduction, data display, and verification. The results showed that the principles of the kingdom of God were applied in the GBI ROCK congregation family of the satellite Kota of Denpasar